2012
DOI: 10.1177/0333102412458190
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use in cluster headache patients and in the general population: A comparative cross-sectional survey

Abstract: The results of this study indicate that male CH patients are prone to overindulge in illicit drug use. This finding possibly reflects a common biological susceptibility that predisposes these subjects to CH and to addictive behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
2
32
0
2
Order By: Relevance
“…Adjusted HR 5.6% vs. controls but not different from those with migraine; number of bouts/year of CH a risk factor for depression.Study limited to patients diagnosed by neurologist and prescribed standard CH drugs; excluding those with previous psychiatric diagnoses (104 of original 777; 13%).Pietrini, 2005 [19]60 consecutive male and female CH patients seen at an Italian headache centerCross-sectional, based on study examination35% had hypertension, defined as blood pressure ≥ 140/90 on average of 3 blood pressure readings.The authors concluded that the prevalence of hypertension in this group was within expected range given age and sex.Robbins, 2012 [20]49 consecutive male and female CH patients seen in a New York headache clinic over a 3.5 year periodCross-sectional chart reviewPrevalence of depression (PHQ ≥ 1 0) was 6.3% in episodic CH, 11.8% in chronic CH; Anxiety (GAD-7 ≥ 10) prevalence was 15.6% in episodic CH and 11.8% in chronic CH. Prevalence of hypertension was 14%, current or former cigarette smoking was 65.3% and GERD was 8%.Rossi, 2012 [21]210 consecutive male and female CH patients from two Italian headache centersCross-sectional interview and anonymous survey data92.5% of male CH patients and 85.4% of female CH patients reported current or past use of tobacco, statistically significantly higher than prevalence in general population.Self reported data on substance use.Rozen, 2012 [22]1134 US male and female CH patients responding to an internet surveyCross-sectional survey (internet)Prevalence of depression was 24%, suicidal ideation was reported by 55%, sleep apnea by14%, restless leg syndrome by 11%, asthma by 9%. 73% were current or former smokers; 51% had been smoking at the time CH began.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusted HR 5.6% vs. controls but not different from those with migraine; number of bouts/year of CH a risk factor for depression.Study limited to patients diagnosed by neurologist and prescribed standard CH drugs; excluding those with previous psychiatric diagnoses (104 of original 777; 13%).Pietrini, 2005 [19]60 consecutive male and female CH patients seen at an Italian headache centerCross-sectional, based on study examination35% had hypertension, defined as blood pressure ≥ 140/90 on average of 3 blood pressure readings.The authors concluded that the prevalence of hypertension in this group was within expected range given age and sex.Robbins, 2012 [20]49 consecutive male and female CH patients seen in a New York headache clinic over a 3.5 year periodCross-sectional chart reviewPrevalence of depression (PHQ ≥ 1 0) was 6.3% in episodic CH, 11.8% in chronic CH; Anxiety (GAD-7 ≥ 10) prevalence was 15.6% in episodic CH and 11.8% in chronic CH. Prevalence of hypertension was 14%, current or former cigarette smoking was 65.3% and GERD was 8%.Rossi, 2012 [21]210 consecutive male and female CH patients from two Italian headache centersCross-sectional interview and anonymous survey data92.5% of male CH patients and 85.4% of female CH patients reported current or past use of tobacco, statistically significantly higher than prevalence in general population.Self reported data on substance use.Rozen, 2012 [22]1134 US male and female CH patients responding to an internet surveyCross-sectional survey (internet)Prevalence of depression was 24%, suicidal ideation was reported by 55%, sleep apnea by14%, restless leg syndrome by 11%, asthma by 9%. 73% were current or former smokers; 51% had been smoking at the time CH began.…”
Section: Introductionmentioning
confidence: 99%
“…Rossi et al (1) show that patients suffering from cluster headache (CH) have a greater prevalence of both lifetime sustained intensive use of illicit drugs and of current intensive use of cannabis as compared to healthy controls. At first glance, these findings seem in line with the well-documented abuse of nicotine (80% smokers as compared to 35% in the general population) (2), relatively high coffee consumption and the finding that 26% of cluster patients regularly use cannabis (3).…”
mentioning
confidence: 99%
“…Regarding the first issue, it is intriguing that Rossi et al (1) found that significant misuse of illicit drugs only holds true for male, but not for female cluster patients. One could argue that the sample size of 210 patients (48 females) is too small for proper statistics, but it is more likely that it is indeed the male cluster patients who are more prone to addictive behaviour.…”
mentioning
confidence: 99%
“…Une consommation excessive d'alcool était antérieurement considérée comme un facteur de risque de l'AVF, mais les données les plus récentes ne l'ont pas confirmé, d'autant qu'un nombre important de patients souffrant d'AVF en période douloureuse évite la consommation d'alcool, cette dernière pouvant déclencher les crises (grade C) [13]. Récemment, une consommation régulière ou occasionnelle de drogues illicites, comme le cannabis et la cocaïne, a également été décrite comme plus importante chez les hommes souffrant d'AVF (grade C) [15]. Des données similaires ont été rapportées en France concernant le cannabis (grade C) [16].…”
Section: Facteurs De Risqueunclassified